2002
DOI: 10.1002/ijc.10768
|View full text |Cite
|
Sign up to set email alerts
|

Possible transient adaptive response to mitomycin C in peripheral lymphocytes from thyroid cancer patients after iodine‐131 therapy

Abstract: Our study attempted to assess the possible induction and persistence of an adaptive response in lymphocytes of thyroidectomized thyroid cancer patients treated with 131 I (2,590 MBq, corresponding to whole body doses in the range of 200 -300 mGy), to a testing dose of mitomycin C (MMC) in vitro. The cytogenetic endpoint studied was the induction of micronuclei in cytokinesis-blocked peripheral blood lymphocytes, immediately before treatment and 1, 6 and 24 months after therapy. One month after therapy, inducti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 42 publications
0
5
0
1
Order By: Relevance
“…Standard therapies for NPC remain toxic and ineffective ( 26 ). I-131 is known as producing relatively low radiation, and has exhibited anti-cancer effects in several types of human cancer, including thyroid and hepatocellular cancer ( 10 – 12 ). In addition, targeted therapy of LEB has presented the potential to completely eradicate tumors, but with low toxicity to normal human tissues during cancer treatment ( 27 , 28 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Standard therapies for NPC remain toxic and ineffective ( 26 ). I-131 is known as producing relatively low radiation, and has exhibited anti-cancer effects in several types of human cancer, including thyroid and hepatocellular cancer ( 10 – 12 ). In addition, targeted therapy of LEB has presented the potential to completely eradicate tumors, but with low toxicity to normal human tissues during cancer treatment ( 27 , 28 ).…”
Section: Discussionmentioning
confidence: 99%
“…Iodine-131 (I-131) therapy has been accepted for the treatment of thyroid cancer due to lower radiation of β-radial and easy excretion. A number of reports have focused on I-131 therapy for the treatment of thyroid cancer ( 10 , 11 ). The efficacy of I-131 has been previously investigated for fewer side effects for patients with cancer.…”
Section: Introductionmentioning
confidence: 99%
“…We have previously demonstrated that therapy with 70 mCi 131 I in DTC patients is consistently associated with increased DNA damage levels in peripheral lymphocytes [22,23]. With this study, we aimed to confirm, through the use of the cytokinesis-blocked micronucleus (CBMN) assay, our prior findings in a new group of DTC patients submitted to RAI therapy with 100 mCi.…”
Section: Introductionmentioning
confidence: 65%
“…Âïëèâ íàâ³òü ìàëèõ äîç ðàä³àö³¿ ñóïðîâîäaeóºòüñÿ ðîçâèòêîì íèçêè çì³í â ³ìóíí³é ñèñòåì³ íà êë³òèííîìó òà ñóáêë³òèííîìó ð³âíÿõ, à äåôåêòè, ùî ñôîðìóâàëèñÿ, ëåaeàòü â îñíîâ³ ïàòîãåíåçó áàãàòüîõ çàõâîðþâàíü. Òàê, ó ë³ìôîöèòàõ êðîâ³ õâîðèõ, ÿê³ ïðîéøëè ë³êóâàííÿ ðàä³îàêòèâíèì éîäîì, âèÿâëåíî ð³çíîìàí³òí³ õðîìîñîìí³ ïîøêîäaeåííÿ, ùî çáåð³ãàþòüñÿ ðîêàìè [7][8][9]. Íàâ³òü íèçüê³ äîçè ðàä³îéîäó, ùî âèêîðèñòîâóþòüñÿ äëÿ ä³àãíîñòè÷íî¿ ñöèíòèãðà-ô³¿, ñóòòºâî çá³ëüøóþòü ê³ëüê³ñòü õðîìîñîìíèõ àáåðàö³é.…”
Section: рівень комплексів антиген-антитіло у хворих на рак щитоподібunclassified